Հայաստանի Հանրապետության ջրային պաշարների ավելացման հնարավորությունները - Առաքելյան, Ս. Ա. (Մանկավարժ հրատ․)
Քաղցրահամ ջրի պաշարների լրացումը լրջագույն խնդիր է աշխարհի բազմաթիվ երկրների, այդ թվում նաև Հայաստանի համար։ Ջրի լրացուցիչ քանակ կուտակելու համար առաջարկվում է հանրապետության տարածքում կառուցել փոքր տարողությամբ մի շարք ջրամբարներ։ Արփա գետի գարնանային վարարումներից ավելացած ջրի քանակը, վաղ գարնանը և աշնանը գետով անտեղի հոսող ջրերը, գետի էկոհամակարգը ապահովող ջրի քանակը ապահովելուց հետո մնացած «ավելորդ» ջրերը Կեչուտի ջրամբարից խողովակաշարով տեղափոխել Արարատյան դաշտ, նույնիսկ մինչև Մերձերևանյան տարածքներ։ Ресурсы пресной воды необходимы для любой страны, в том числе и для Республики Армения. Армения расположена в полупустынной зоне субтропического пояса и характеризуется сухим континентальным климатом. И возникает вопрос: как увеличить водные ресурсы нашей страны при наличии как поверхностных, так и подземных вод. Учитывая, что снеговые и дождевые осадки в водосборах рек Арпа-Воротан, в высокогорных районах количество снегопадов превышает количество выпавших осадков, предлагается: • на крутых склонах снег накапливается в каньонах с искусственно созданными сугробами. Образовавшиеся таким образом скопления снега будут иметь небольшую поверхность и большую толщину, что надолго обеспечат реки дополнительными запасами воды. Искусственные лавины могут быть вызваны взрывами малых зарядов, а также другими способами. В первую очередь, это должно быть сделано за счет снега, накопившегося на восточных и южных склонах гор, так как снег на этих склонах быстро тает. Таким образом можно увеличить количество воды, протекающей через реки, и количество грунтовых вод. На Арагаце, в глубоких долинах Гегамских гор, дополнительное количество снега увеличит водные ресурсы Араратского артезианского бассейна. Перекачиваемая вода должна быть использована для пополнения водохранилища на реках Веди и Азат. В остальное время для рационального использования воды, поступающей в Араратскую долину, необходимо построить небольшие водохранилища (3–3,5 млн м3) и решить проблему орошения земель многих сел. За счет накопления снега можно увеличить сток воды в озеро Севан. И каждый год у нас в озере Севан будет запас воды. Freshwater resources are essential for any country including for the Republic of Armenia. According to the geographical zoning, Armenia is located in the semi-desert zone of the subtropical area. The demand for water is high in the dry field of Ararat and in Vayots Dzor region. But the situation is not good in other regions, too. 62 % of the precipitation on our earth evaporates due to the arid climate. The rest of the water flows through deep river gorges and irrigated lands remain at higher levels. And there arises the question: how to increase the water resources of our country in case of both surface flow and groundwater. Taking into account, that the snow and rain precipitation in the catchmants og the Arpa-Vorotan rivers, in the high mountainous regions, the amount of snowfall exceeds the amount of rain fall, it is offered: · on steep slopes snow accumulates in the canyons with artificially generated snowdrifts. The accumulations of snow formrd in this way will have a small surface and large thicjness, and will give the rivers extra water melting for a long time. Artificial avalanches can be caused by small-charge explosions, as well as in other ways. First of all, this should be done first of all at the expense of the snow accumulated on the eastern and southern slopes of the mountains, as the snow melts quickly on those slopes. In this way it is possible to increase the amount of water flowing through rivers and the amount of groundwater. In Aragats, in the deep valleys of the Geghama mountains, the additional amount of snow will increase the water resources of the Ararat artesian basin. In addition to the water transported from the Kechut reservoir from the Arpa-Sevan water tunnel to Sevan Lake, we will have free water resources by increasing the water of the Arpa River tributaries. It is suggested to move it to Ararat plain. It is taken into account that the Kechut reservoir has a much higher absolute height than the Urts mountain range near Zangakatun, the water can be transported by gravity through the pipeline to the Ararat valley. The transferred water should be used to provide additional water to the reservoir on the Vedi and Azat rivers. For the rest of the time, for the rational use of the water transferred to the Ararat Valley, it is necessary to build small reservoirs (3-3.5 million m3)1and to solve the problem of irrigation of the lands of many villages. Due to the accumulation of snow, it is possible to increase the water flow to Lake Sevan. And every year we will have extra water in Lake Sevan.
Keywords: Աշխարհագրություն; Ջրային ռեսուրսներ